A sensitive MnO2 nanosheet sensing platform based on a fluorescence aptamer sensor for the detection of zearalenone. Issue 46 (23rd November 2022) - Qin, Guoxin; Wei, Yuanwen; Zhou, Qifeng; Wang, Haijun; Wei, Yuning; Lao, Shuibing; Luo, Lihong; Mo, Renfu; Chen, Yongxian; Yang, Yuxia; He, Jie; Li, Huiling
Abstract : An aptamer sensor based on manganese dioxide (MnO2 ) nanosheets was developed for the detection of zearalenone (ZEN). Abstract : An aptamer sensor based on manganese dioxide (MnO2 ) nanosheets was developed for the detection of zearalenone (ZEN). The ZEN aptamer was modified at the 5′-end by a 6-carboxyfluorescein (6-FAM) fluorophore with self-assembly on MnO2 nanosheets. Interaction of the 6-FAM fluorophore at the 5′-end of the ZEN aptamer with the MnO2 nanosheet lowered fluorescence (FL) intensity due to fluorescence resonance energy transfer (FRET). The introduction of ZEN into the sensing system resulted in hybridization with the ZEN aptamer, forming a stable G-quadruplex/ZEN, which exhibited a low affinity for the MnO2 nanosheet surface. The distance between the 6-FAM fluorophore and MnO2 nanosheet hampered FRET, with a consequent strong FL signal. Under the optimal experimental conditions, the FL intensity of the sensing system showed a good linear correlation with ZEN concentration in the range of 1.5–10.0 ng mL −1, and a detection limit (S/N = 3) of 0.68 ng mL −1 . The sensing system delivered enhanced specificity for the detection of ZEN, and can find wide application in the detection of other toxins by replacing the sequence of the recognition aptamer.